THE EFFECT OF THE MARKETING MIX STRATEGY ON CONSUMER BUYING INTEREST IN SMALL AND MEDIUM MICRO BUSINESSES (UMKM) KAMPUNG LALANG STOP KINOY - Winda Hardiyanti Damanik, Sri; Vera Dewi, Kumala; Purba, Rakhmawati (RADJA PUBLIKA, 2022)
This study aims to determine the effect of Marketing Mix on consumer buying interest in Micro, Small and Medium Enterprises (MSMEs) at Warung Kinoy Kampung Lalang. This type of research is explanatory research. The sample in this study were 96 respondents. The sampling technique used is proportional sampling. The test tool used is multiple linear regression analysis. The results of this test conclude that price and promotion have an effect on consumer buying interest while product and place have no effect on consumer buying interest.